Adaptive digital watermarking algorithm under image quad-tree partition - Wen-xing LIU; Wei CHEN; Yuan LIU (网络与信息安全学报)
An adaptive digital watermarking algorithm based on image quad-tree partition was proposed.The original image was approximated by various least square polynomial patches at multiple scales and was organized by a quad-tree structure.At the same time,this representation also reflected the texture information of image.By calculating the watermark embedding intensity in different regions,an adaptive digital watermarking scheme based on the number of the refined meshes in each region was realized.The experiment results show that this algorithm has the good imperceptibility and robustness.